Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.pedneo.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rewarming in oxygenation and respiratory condition after neonatal exposure to moderate therapeutic hypothermia

Abstract: Background: To assess changes in clinical condition and oxygenation in neonates after rewarming following moderate therapeutic hypothermia (MTH) for neonatal encephalopathy. Methods: Retrospective study of 28 neonates receiving MTH in a tertiary neonatal intensive care unit in Israel. We compared pre-and 24 h post-rewarming arterial oxygen saturation (SaO 2) as measured by the blood gases analyzer, pulse-oximetry saturation (SpO 2), and cardiorespiratory condition. Results: The SpO 2 declined from 96.9% (AE2.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
0
3
1
Order By: Relevance
“…Of this cohort, 12 neonates had respiratory impairment as shown by higher inspired oxygen requirements or increased desaturations. Of the 18 infants without need for respiratory support, 16 showed a fall in arterial and peripheral oxygen saturation following rewarming 14 . However, in contrast to the present study, no infants in that cohort had new onset need for respiratory support after rewarming.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Of this cohort, 12 neonates had respiratory impairment as shown by higher inspired oxygen requirements or increased desaturations. Of the 18 infants without need for respiratory support, 16 showed a fall in arterial and peripheral oxygen saturation following rewarming 14 . However, in contrast to the present study, no infants in that cohort had new onset need for respiratory support after rewarming.…”
Section: Discussioncontrasting
confidence: 85%
“…Dassios et al reported that arterial oxygen saturation and arterial oxygen tension tended to increase during cooling and decrease at rewarming, albeit this was statistically insignificant, and conversely fractional inspired oxygen increased after rewarming 13 . Of potential concern, decreased oxygenation after rewarming from TH was reported in 28 infants 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jain et al [115] To evaluate and compare early EEG power and EEG as predictors of MRI injury in neonatal HIE. PLOS ONE PLOS ONE sedation but do not mention the agent used [32,40,[44][45][46], while two studies use generic names such as "opiates" and "benzodiazepines" instead of identifying the specific medication [47,48]. Table 2 lists the different dose ranges of medications used.…”
Section: Prospective Cohort Study N = 44 Questionmentioning
confidence: 99%